2022
DOI: 10.3389/fneur.2022.880046
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Endovascular Thrombectomy in Pre-stroke Dependent Patients With Acute Ischemic Stroke: A Systematic Review and Meta-Analysis

Abstract: IntroductionEndovascular thrombectomy (EVT) is a well-established and effective therapeutic option for patients that meet certain criteria. However, this modality is not well studied in patients with pre-existing disability. The aim of the present study was to investigate the impact of mechanical thrombectomy in patients with acute onset ischemic stroke and pre-stroke dependency (PSD) in regard to their clinical outcome and mortality.Materials and MethodsThe MEDLINE, Scopus, and Cochrane Library databases were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Even though pre-stroke disability was associated with higher mortality and worse neurological functional outcomes at 3 months, the use of IV thrombolysis appeared to be of benefit to some previously dependent patients ( 21 ). A recent meta-analysis of five observational studies of MT concluded a “good clinical outcome,” which was defined as an mRS score of 0–2 or a return to the pre-stroke mRS score in 27% of patients at 3 months ( 10 ). However, the analysis was not restricted to older patients, thus explaining that the mean age was lower than in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though pre-stroke disability was associated with higher mortality and worse neurological functional outcomes at 3 months, the use of IV thrombolysis appeared to be of benefit to some previously dependent patients ( 21 ). A recent meta-analysis of five observational studies of MT concluded a “good clinical outcome,” which was defined as an mRS score of 0–2 or a return to the pre-stroke mRS score in 27% of patients at 3 months ( 10 ). However, the analysis was not restricted to older patients, thus explaining that the mean age was lower than in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Older patients have been poorly represented in randomized clinical trials while they have a less favorable functional outcome after stroke ( 4 ). Nevertheless, they seem to benefit as much as young patients from both IVT ( 5 , 6 ) and MT ( 7 10 ) regarding 3- and 6-month outcomes ( 6 9 ) but few studies described long-term outcomes ( 11 ). In addition, patients with a prior-to-stroke disability defined as a pre-morbid modified Rankin scale (mRS) score ( 12 ) of either >2 or >3 were excluded from most trials of acute IS revascularization therapy, regardless of age.…”
Section: Introductionmentioning
confidence: 99%
“…Future work in pre-hospital and hospital settings should also consider combining physiological factors with other nonstroke characteristics which may have a bearing on thrombectomy outcome such as frailty, pre-stroke dependency and comorbidities (Adamou et al, 2022;Tan et al, 2022;Barow et al, 2023). Although some have been included in previously published thrombectomy outcome scores (Kremers et al, 2021), especially pre-stroke dependency, it has not yet been demonstrated that they are accurate when used by non-specialist practitioners making early triage decisions towards thrombectomy providers.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis of six observational studies including 591 patients with pre-stroke dependency found a higher rate of unfavourable clinical outcome and a higher mortality rate when undergoing endovascular treatment than in those with no previous disability. 101 However, a substantial proportion of these patients recovered well after treatment, indicating possible benefit in selected patients. More data from randomised controlled trials are needed, and investigators should reconsider what constitutes a so-called good outcome.…”
Section: Future Directionsmentioning
confidence: 98%